Proceedings of IEEE 48th Annual Symposium on Frequency Control
DOI: 10.1109/freq.1994.398312
|View full text |Cite
|
Sign up to set email alerts
|

Designing smaller SAW oscillators for low vibration sensitivity

Abstract: All quartz package (AQP) Surface Acoustic Wave (SAW) hybrid circuit oscillators with low vibration sensitivity, typically 3 to 4~1 0 -'~/ g , have been routinely achieved, provided that the oscillator package is sufficiently rigid to minimize bending stresses caused by vibration loading. This has been accomplished by bonding a suitably thick ceramic stiffener to the base of the oscillator housing. However, because of size constraints, some applications cannot accommodate a sufficiently thick stiffener. One app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The third example is a plane strain problem. In this experiment by-Andres and Parker, it was shown that by properly massloading the backside of an all quartz package (AQP) SAW substrate that the bending stresses caused by a normal acceleration could be minimized [6]. Modeling this situation meant that the dimensions of concern were the length and thickness of the substrate which were 10.16 mm and 0.89 mm respectively, the length of the active SAW area was 0.5 mm.…”
mentioning
confidence: 99%
“…The third example is a plane strain problem. In this experiment by-Andres and Parker, it was shown that by properly massloading the backside of an all quartz package (AQP) SAW substrate that the bending stresses caused by a normal acceleration could be minimized [6]. Modeling this situation meant that the dimensions of concern were the length and thickness of the substrate which were 10.16 mm and 0.89 mm respectively, the length of the active SAW area was 0.5 mm.…”
mentioning
confidence: 99%